Electrical pulse stimulation reflecting the episodic nature of real-life exercise modulates metabolic and secretory profile of primary human myotubes - Gabrišová, Klára; Kurdiová, Tímea; Barkova, Daria; Pálešová, Natália; Babulicová, Jana; Tyčiaková, Silvia; Novotová, Marta; Balážová, Mária; Sabo, Miroslav; Pustka, Václav; Ukropec, Jozef; Ukropcová, Barbara (FEBS open bio, 2026)
Electrical pulse stimulation (EPS) represents a useful tool to study exercise-related adaptations of muscle cells in vitro. Here, we examine the metabolic and secretory response of primary human muscle cells from metabolically healthy individuals to the EPS protocol reflecting the episodic nature of real-life exercise training. This intermittent EPS protocol alternates high-frequency stimulation periods with low-frequency resting periods. Continuous EPS was used as a comparator. Radiometric assessment of glucose and fatty acid metabolism was complemented by examination of mitochondrial OxPHOS proteins, fiber-type markers, and the release of selected myokines and extracellular vesicles into the media. Both EPS protocols facilitated glycogen synthesis and incomplete fatty acid oxidation (intermediary metabolites accumulation), while complete glucose and fatty acid oxidation (CO2 production) was increased only after the intermittent stimulation. Continuous stimulation elicited robust release of the contraction-regulated myokines (IL6, IL8) into the media. Both EPS protocols increased expression of oxidative fiber-type markers (MYH2, MYH7), while inducing protein expression of a putative myokine, growth differentiation factor11 (GDF11) and a release of extracellular vesicles into the media. In conclusion, intermittent electrical pulse stimulation enhanced the rate of complete glucose and fatty acid oxidation in differentiated muscle cells from metabolically healthy individuals, while it was comparable to continuous stimulation in modulating markers of oxidative fibers and a putative myokine GDF11, and less effective in stimulating the release of myokines IL6, IL8, and extracellular vesicles into the media. Intermittent EPS-a protocol mimicking the episodic nature of exercise-can be used for studying metabolism and the secretome of skeletal muscle cells in vitro.
Keywords: mastné kyseliny; dospělí; extracellular vesicles; cvičení; human primary muscle cell culture; lidé; kultivované buňky; Cells, Cultured; elektrická stimulace; electrical pulse stimulation; Exercise; Humans; kosterní svalová vlákna; kosterní svaly; myokines; mužské pohlaví; Glucose; Adult; Male; Fatty Acids; Muscle, Skeletal; Electric Stimulation; growth differentiation factor 11; Muscle Fibers, Skeletal; glukosa; glucose and fatty acid metabolism